STRATEGI INOVASI DAN KINERJA INDUSTRI RUMAHAN DALAM MENINGKATKAN MINAT PEMBELIAN KONSUMEN DI PASAR SUKARAMAI MEDAN - Arasy Ayu Setiamy; Etika Deliani (Jurnal Ilmu Manajemen METHONOMIX, 2019)
Human resources in organizations play an important role in shaping a company's goals. One of the tasks of management is to develop human resources in a way so that humans can be integrated effectively into the various organizations needed by society. Buying interest is a mental statement of consumers that reflects the purchase plan of a product with a specific brand of knowledge about consumer buying potential for the product. It needs to be known by marketers to describe consumer behavior in the future. The research aims to examine the effect of innovation and home industry performance on buying interest in Suka Ramai Market Medan.